A randomized clinical study evaluating effects of high-intensity interval training on myocardial microvascular dysfunction. (14th October 2021) - Rafique, M; Solberg, O G; Gullestad, L; Bendz, B; Rolid, K; Nytroen, K; Lunde, K
Abstract: Background: Myocardial microvascular function assessed with the Index of Microcirculatory Resistance (IMR) after heart transplantation (HTx) predicts the development of cardiac allograft vasculopathy (CAV) and adverse long-term outcome. This study aimed to evaluate the otherwise beneficial effects of high-intensity interval training (HIT) on microvascular dysfunction development. Methods: Eighty-one de novo HTx patients were randomized to nine consecutive months of HIT or standard care rehabilitation. Coronary physiology assessment with a pressure wire was performed in the left anterior descending coronary artery. IMR was calculated by multiplying the mean distal coronary pressure by the mean hyperemic transit time. Results obtained at three and twelve months after HTx were compared to assess the treatment effect of HIT. Results: Results were available for 60 patients. 71% were men, and the mean age was 48±13. IMR in the HIT group (n=26) decreased from 14.8±9.5 to 13.8±8.0, change = 1.2, 95% CI [−2.6 to 4.9] and increased in the standard care group (n=34) from 13.8±5.8 to 16.8±12.0, change = −3.5, 95% CI [−7.1 to 0.1]. The mean difference between groups was 4.7, 95% CI [−9.7 to 0.4], p=0.07. Conclusion: These results suggest that early initiation of HIT improves microvascular function. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Stiftelsen Dam